Practice follows structure : QM in Malaysian public hospitals - Abd. Manaf, Noor Hazilah (Emerald, 2009)
Purpose – The main aim of this study is to provide an empirical analysis on the practice of quality management among employees of Malaysian public hospitals at the district, state and national level hospitals. This paper aims to perform a comparative analysis on quality management practices among the three levels of hospitals. Design/methodology/approach – The main method of data collection was self-administered questionnaire, and cluster sampling was used to select the respondent hospitals, while respondent employees were selected by stratified random sampling. Altogether 23 public hospitals throughout Peninsular Malaysia participated in the survey. Findings – Practice of quality management was found to be significantly higher in district hospitals than in the national referral centre. However, there was no significant difference in perception on implementation outcome between the three levels of hospitals. Among the factors of quality management, teamwork was found to be significantly higher in district hospitals than in state hospitals and the national referral centre. Leadership and management commitment were found to be significantly higher in district and state hospitals than in the national referral centre. The effect of organizational structure could have an effect on practice of quality management. Originality/value – Empirical studies on the effect of organisational structure on practice of quality management among employees of Malaysian public hospitals have never b